: UPAYA PENANGANAN SCABIES PADA PASIEN LAKI LAKI USIA 9 BULAN MELALUI PENDEKATAN KEDOKTERAN KELUARGA DI PUSKESMAS MUARA BATU KABUPATEN ACEH UTARA - Adri (Yayasan Pendidikan Medika Indonesia, 2026)
Patient An. MKM was brought by his mother to the Maternal and Child Clinic at Muara Batu Primary Health Center with complaints of erythematous papules accompanied by skin desquamation, itching, and pain in the interdigital areas of the hands, feet, and genital region for approximately 3 months. The symptoms worsened at night and during sweating, with the patient frequently scratching, becoming irritable, and crying. Initially, the lesions appeared between the fingers and later spread to other body areas. Some lesions ruptured due to scratching without pus formation. Assessment was carried out through alloanamnesis and physical examination. The clinical findings were suggestive of a skin infection such as scabies. Interventions included education on personal and environmental hygiene, avoidance of scratching, and the use of topical medications along with adherence to regular treatment to prevent transmission. Primary data were obtained through alloanamnesis and physical examination during home visits, accompanied by family data collection and medical record documentation. Evaluation was conducted using a holistic diagnostic approach covering the initial, process, and final stages of care, both quantitatively and qualitatively. Interventions also included family education, lifestyle modification advice, and appropriate disease management